Accepting a reduced self after acute trauma - Lison-Pick, Mandy (Curtin University, 2011)
Disability associated with loss of limb function following major/minor trauma is a life-changing phenomenon of global significance which poses a heavy burden on healthcare systems, communities and individuals. While there is a voluminous and growing body of knowledge on disabilities and chronic illness, little attention has been given to the short and long-term experiences of those living with loss of limb function and disability following acute major and minor trauma. The aim of this thesis is to develop a substantive theory that describes the phenomenon of living with disabilities resulting from a loss of limb function from acute minor or major trauma.Data were obtained from face-to-face interviews with 15 consenting participants aged between 18-45 years who had lost limb function from acute major/minor trauma all of whom were attending the Pain Management Centre of a major teaching hospital in Western Australia. Four clinical practitioners (who were classed as experts in their field) were also interviewed to clarify the practices the participants discussed so an all round picture could be given and analysed. Data analysis was conducted using the constant comparative technique of the Grounded Theory Method. The results indicate that the basic social problem was Loss of Self and developed from either a sudden or gradual loss of limb function as a result of acute trauma. This trauma had a biopsychosocial impact as the participant’s hospitalisations, surgical procedures, extended rehabilitation programs and resultant disability reduced the self.The basic social process experienced was recognised as Accepting a Reduced Self appearing in three stages: Floundering, Treading Water and Wading to Shore. However these stages were strongly influenced by various modifying conditions such as their persistent pain, the availability of a support crew, the type of trauma experienced and the length of time since injury. It was concluded that disabilities related to loss of limb function can occur following acute major or minor trauma. The impairment the participants experienced affected all aspects of their lives and that of their partners, family and friends as most of them continued to struggle with their disability, either biologically, psychologically or socially. The findings of this thesis point to the importance of more research into designing care and offering ongoing support services to provide long term care for this vulnerable, disabled population.